Exosomes and Immune Response in Cancer: Friends or Foes? - Barros, Francisco M.; Carneiro, Fatima; Machado, Jose C.; Melo, Sónia A. (Frontiers in Immunology, 2018)
Exosomes are a type of extracellular vesicle whose study has grown exponentially in recent years. This led to the understanding that these structures, far from being inert waste by-products of cellular functioning, are active players in intercellular communication mechanisms, including in the interactions between cancer cells and the immune system. The deep comprehension of the crosstalk between tumors and the immune systems of their hosts has gained more and more importance, as immunotherapeutic techniques have emerged as viable options for several types of cancer. In this review we present a comprehensive, updated and elucidative review of the current knowledge on the functions played by the exosomes in this crosstalk. The roles of these vesicles in tumor antigen-presentation, immune activation and immunosuppression are approached, as are the relevant interactions between exosomes and the complement system. The last section of this review is reserved for the exploration of the results from the first phase I and II clinical trials of exosomes-based cell-free cancer vaccines.